Pengembangan Modul Praktikum Kimia Terintegrasi Green Chemistry tentang Senyawa Kompleks Co-Ekstrak Kulit Buah Naga Merah - Siti Rumaisah Ramadhani; Agus Abhi Purwoko; Muti'ah Muti'ah (FKIP University of Mataram, 2026)
This research aims to develop and measure the feasibility of a practicum module integrated with green ghemistry about complexion of cobalt with anthocyanin from dragon fruit’s peel extract as a supplementary learning material. This research employed a Research and Development (R&D) Method using 4D model (Define, Design, Develop, and Disseminate). The feasibility of the module is analyized from expert validity test using Aiken’s V formula. The validity test from 6 chemistry expertises show that the module has a very high validity score in all 4 aspects: content, alingment with green chemistry principles, presentation, and clarity of instruction, with V score 0.8867, 0.9425, 0.8875, and 0.8850 respectively. Therefore, the average V score for the module is 0,9004 (highly valid). So, it can be concluded that the module practicum is considered highly feasible to be used as a supplementary instructional material in the Transition Element Compound course